2013
DOI: 10.1590/s0074-02762013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Response to treatment in Brazilian patients with chronic hepatitis C is associated with a single-nucleotide polymorphism near the interleukin-28B gene

Abstract: A single-nucleotide polymorphism (SNP) upstream of interleukin (IL)28B was recently identified as an important predictor of the outcome of chronic hepatitis C patients treated with pegylated interferon plus ribavirin (PEG-IFN/RBV). The aim of this study was to investigate the association between the IL28B gene polymorphism (rs12979860) and virological response in chronic hepatitis C patients. Brazilian patients (n = 263) who were infected with hepatitis C virus (HCV) genotype 1 and were receiving PEG-IFN/RBV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…However, it was not observed by Ferreira et al 31 and Conde et al, 32 two other works made in Brazil. Grandi et al 33 in a population from south Brazil reported that the rs12979860 CC genotype was significantly associated with higher treatment response rates and a lower relapse rate compared to other genotypes. Cavalcante et al 34 confirmed this result in a population from northeast Brazil, where IL-28B rs12979860 CC was associated with SVR, and the CT or TT genotypes were associated with failure of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not observed by Ferreira et al 31 and Conde et al, 32 two other works made in Brazil. Grandi et al 33 in a population from south Brazil reported that the rs12979860 CC genotype was significantly associated with higher treatment response rates and a lower relapse rate compared to other genotypes. Cavalcante et al 34 confirmed this result in a population from northeast Brazil, where IL-28B rs12979860 CC was associated with SVR, and the CT or TT genotypes were associated with failure of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and follow-up - The 263 patients enrolled in this study were the same individuals who participated in a previous study ( Grandi et al 2013 ). Briefly, the study population consisted of 154 males (48.0 ± 10.4 years old) and 109 females (55.5 ± 10.3 years old) living in the southernmost state of Brazil (Rio Grande do Sul).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…A recent study from our laboratory has shown that the response to treatment in Brazilian patients with hepatitis C was associated with a SNP near the IL-28B gene ( Grandi et al 2013 ). The aim of the present study, which was performed with the same group of patients (n = 263), was to determine whether IL-10, TNF and Mx1 gene promoter polymorphisms are relevant for the response to PEG-IFN/RBV therapy.…”
mentioning
confidence: 99%
“…genótipo C/C apresenta melhor RVS, quando comparado aos C/T e T/T (102;145) . Em nosso estudo o genótipo C/T foi o mais comum, encontrado em 56% dos pacientes, seguido do genótipo C/C (34%) e, com menor frequência, T/T (10% (146) . No estado do Rio de Janeiro, região mais próxima a Ribeirão Preto, Ramos et al encontraram em 66 pacientes cronicamente infectados pelo HCV uma frequência de 32%…”
Section: Discussionunclassified